2021
DOI: 10.1113/ep089433
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of testosterone‐dependent erythropoiesis during male puberty

Abstract: The amount of haemoglobin during puberty is related to endurance performance in adulthood. During male puberty, testosterone stimulates erythropoiesis and could therefore be used as a marker for later endurance performance. This cross-sectional study aimed to determine the relationship between serum testosterone concentration and haemoglobin mass (Hbmass) in both male and female children and adolescents and to evaluate the possible influences of altitude and training. Three-hundred and thirteen differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
2
21
2
1
Order By: Relevance
“…Finally, possible differences in terms of hematological and performance parameters between children and adolescents in different sports disciplines at different altitudes should be pointed out. In a first, recently published step, we showed the normal course of the increase in Hbmass during puberty in male and female adolescents and the influence of the increasing testosterone concentration in boys (Mancera-Soto et al, 2021). The work presented here represents the main part of the study and, in addition to the normal development of Hbmass, BV and VO 2 max in children and adolescents, describes the influence of training status and different altitudes on the above parameters and their interactions.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Finally, possible differences in terms of hematological and performance parameters between children and adolescents in different sports disciplines at different altitudes should be pointed out. In a first, recently published step, we showed the normal course of the increase in Hbmass during puberty in male and female adolescents and the influence of the increasing testosterone concentration in boys (Mancera-Soto et al, 2021). The work presented here represents the main part of the study and, in addition to the normal development of Hbmass, BV and VO 2 max in children and adolescents, describes the influence of training status and different altitudes on the above parameters and their interactions.…”
Section: Introductionmentioning
confidence: 67%
“…In total, 475 healthy children and adolescents (girls n = 217, boys n = 258; untrained group n = 171, endurance trained group n = 304) living at two different altitudes (~1,000 m, n = 204, ~2,600 m, n = 271) and aged from 9 to 18 years old participated in the study. Data on Hbmass and BV in relation to serum testosterone and erythropoietin concentrations were already determined from 313 participants in a recent publication (Mancera-Soto et al, 2021). Hematological data were recorded for all 475 children, and maximum oxygen uptake (VO 2 max) was determined in 404 participants.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of testosterone causes a rightward shift in the EPO-Hb relationship curve as well as a new physiological "set point" (Bachman et al, 2014). Mancera-Soto et al (2021), claims that during the most sensible phase of puberty, an increase in testosterone plasma of 1 ng/ml is correlated to an increase in hemoglobin mass of ~65 g. The effects of testosterone on individual variability in men compared to women; however, is currently unknown and would require further examination. Furthermore, Goodrich et al (2020) demonstrated that variations in hemoglobin mass across groups of varying athleticism and sex were more closely related to lean body mass than whole body mass.…”
Section: Sexmentioning
confidence: 99%
“…Although they raise the challenge of establishing causality from cross‐sectional studies in their limitation section, we are surprised they still conclude that endurance training yields an additional effect on cardiovascular changes during puberty over those driven by growth and maturation alone. It is undisputed that puberty exerts significant physiological changes on the growing child, mainly driven by altered circulating hormones that stimulate increased lean body mass and changes in haemoglobin mass (Hb mass ) and blood volume (Baxter‐Jones, 2017; Landgraff & Hallén, 2020; Landgraff et al., 2021; Mancera‐Soto et al., 2021; Rogol et al., 2002). If and to what extent endurance training causes additional haematological and cardiovascular changes beyond those driven naturally by growth and maturation is still uncertain and can only be assessed convincingly by randomized controlled trials or longitudinal study designs.…”
mentioning
confidence: 99%